Importancia del análisis financiero de liquidez, solvencia, gestión, rentabilidad y su influencia al solicitar un crédito. - Barros Bermeo, Cinthya Maria (My University, 2019)
In this case study, the importance of the analysis of the financial indicators is developed, in order to identify if the results obtained influence the decision making of the financial system applied to the company CARTOPEX S.A. dedicated to the commercialization of household appliances. Twenty formulas are applied for its development, which are divided into four ratios, liquidity, solvency, management and profitability. The methodology implemented will be the conceptualization of the four indicators as well as the accounting calculation of each of them and thus be able to issue a timely financial analysis. The results have shown that the company in general mentioning its indicators are low, however there is a possibility that you will obtain a loan that will help you obtain working capital and continue with your future investments.
En este caso práctico se desarrolla la importancia del análisis de los indicadores financieros, con el objetivo de identificar si los resultados obtenidos influyen en la toma de decisiones del sistema financiero aplicado a la empresa CARTOPEX S.A. dedicada a la comercialización de electrodomésticos. Para su desarrollo se aplica veinte fórmulas que están dividas en cuatro ratios, liquidez, solvencia, gestión y rentabilidad. La metodología implementada será la conceptualización de los cuatro indicadores así como el cálculo contable de cada uno de ellos y así poder emitir un análisis financiero oportuno. Los resultados obtenidos han demostrado que la empresa en mención de manera general sus indicadores son bajos, sin embargo existe la posibilidad que obtenga un crédito que le servirá para obtener un capital de trabajo y continuar con sus futuras inversiones.
Keywords: ADMINISTRACIÓN FINANCIERA; ÍNDICES FINANCIEROS; RENTABILIDAD